2021
DOI: 10.1109/access.2021.3064019
|View full text |Cite
|
Sign up to set email alerts
|

Quranic Optical Text Recognition Using Deep Learning Models

Abstract: A Quranic optical character recognition (OCR) system based on convolutional neural network (CNN) followed by recurrent neural network (RNN) is introduced in this work. Six deep learning models are built to study the effect of different representations of the input and output, and the accuracy and performance of the models, and compare long short-term memory (LSTM) and gated recurrent unit (GRU). A new Quranic OCR dataset is developed based on the most famous printed version of the Holy Quran (Mushaf Al-Madinah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…Mohd et al [8] came up with a way to recognize Quranic text using a convolutional neural network (CNN) and a recurrent neural network (RNN). Because they tested it on many data, they found that it had an accuracy rate of 98% on the validation data.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohd et al [8] came up with a way to recognize Quranic text using a convolutional neural network (CNN) and a recurrent neural network (RNN). Because they tested it on many data, they found that it had an accuracy rate of 98% on the validation data.…”
Section: Related Workmentioning
confidence: 99%
“…Beyond that, there are challenges inherent in the Arabic language and a dearth of annotated corpora and resources. For the Arabic language, extracting named entities is quite challenging due to its morphological structure [7,8]. Arabic is a morphologically complex language due to its inflectional nature; it has a general form of a word: prefix(es) + stem + suffix(es), with the number of prefixes and suffixes ranging from 0 to many.…”
Section: Introductionmentioning
confidence: 99%
“…21 Deep learning models have been applied to Arabic based scripts with success proving once again they have virtue. [22][23][24] The CNN architectures are widely used in object recognition tasks including character recognition successfully. An important shortcoming of CNN architectures is that they are not good at recognition of sequences of objects such as the sequences of characters in text.…”
Section: Deep Neural Network Architecturementioning
confidence: 99%
“…Currently, the use of gated recurrent unit (GRU) in pattern recognition can give good results. In recognition of Arabic characters, it is recently used by Mohd [8]. The proposed model uses CNN for the extraction of the features and implements BLSTM and BGRU for the recognition phase.…”
Section: Figure 1: Different Shapes Of Arabic Printed Charactersmentioning
confidence: 99%